Ensuring Emotional Fitness of Healthcare Workers Through Employee Champion Role of Human Resource Management - Manju Nair (ACHSM, 2023)
Objective: The study examines Human Resource champion approach in combating the emotional health problems of healthcare workers. The objectives of the study include identifying the different emotional needs of Health care workers; mapping the various Human Resource Champion roles towards each of the identified emotional needs of the healthcare workers and the different levels of emotional well-being.  Methods: Based on a mini review the purpose of the paper is to create a unique synthesis and proposal for utility of healthcare organizations The exploration included terms of search in combination and in particular related to emotional fitness of healthcare workers, COVID-19, HR role in managing employee stress, , workplace stress, employee champion and HR champion. The potential chances of subjectivity in selection of the papers cannot be overlooked though the various databases used for review include Google scholar, Web of Science, Semantic Scholar which provides the most cited work. Results: The study reports a negative influence of pandemic on HCW's mental health. The identified needs of Healthcare workers during the pandemic include caring, protecting, hearing, preparing and supporting them. The identified needs have been mapped towards the various HR champions ie physical, social, financial, emotional, work-life integration and meaning in work champion. The various practices that were available and were considered feasible have also been evaluated. The fulfillment of the specific emotional needs of HCW's can lead to emotional well- being at different levels including essentials, belonging, purpose and flourishing. Conclusions: The findings of the study reveal that different employee champions can nurture the specific emotional needs of healthcare workers thereby leading to fulfillment of their emotional well-being at different levels. Some champion roles are more visible (Physical and financial champion) as compared to Work- life integration, Social, Emotional, Meaning in work champions in the healthcare organizations.